Enhancing Female Entrepreneurship through Cash Grants : Experimental Evidence from Rural Tunisia - Ferrah, Samih; Gazeaud, Jules; Khan, Nausheen; Mvukiyehe, Eric; Shrotri, Varada; Sterck, Olivier; Zineb, Samir Ben (World Bank, Washington, DC, 2021)
In Tunisia, while social protection and labor programs are in place, severe challenges including inefficiency, fragmentation, and inequity limit the country’s ability to respond to increasing social needs. Gender issues are also one of the critical areas since young women are experiencing even more severe challenges getting into the tight labor market than young men. Unemployment in the MENA region has been a challenge for some time, markedly during the Arab Spring, resulting in the need to create over 50 million jobs in the region in the next decade, to ensure socio-political stability. Unemployment rates are highest in rural and low-income areas. It is in this context that a pilot project of Community Works andLocal Participation (CWLP) was initiated in rural Jendouba in 2015. It was financed by the Japan Social Development Fund (JSDF) through the World Bank and implemented by the Tunisia Republic’s Ministry of Vocational Training and Employment (MVTE). A rigorous randomized control trial (RCT) was embedded in the second phase of the CWLP roll-out (starting in late 2015 and early 2016) and carried out by the World Bank’sDIME Department in partnership with MVET’s ONEQ. The study’s main objective was to capture the effects of CWLP’s cash for work activities. The results of this study, based on a detailed survey of over 4,000 participants and non-participants 6-12 months after completion of project activities, suggested that in general, the CWLP has had positive impacts on the economic well-being of beneficiaries and to a small extent on social and psychological well-being. However, these results also raised concerns that these positive effects may not persist in the long-run, particularly for women who still face huge constraints participating in the tight labor market, which has yet to fully recover to pre-Jasmine revolution levels.